Rock slope stability assessment through rock mass classification systems - Pantelidis, Lysandros (My University, 2009)
Over the last several decades, rock mass classification systems have been proposed in order that cuttings at high risk for failure be identified, and preventive measures be effectively prioritized. The present paper attempts a review of the systems in question, illustrating the main differences and similarities among them, which are focused on the types of failures considered and the factors involved. The reliability of these systems is discussed as well. Relatively, these systems contain factors which raise queries about their suitability or the manner by which they are attributed into them. Moreover, although a rock cut failure event presupposes the action of a triggering factor (e.g., earthquake, precipitation), rock mass classification systems, by omitting it, do not classify cuttings according to their actual hazard (potentiality) for failure. Groundwater, when it is not erroneously ignored, is taken into account as instability factor with limited effect upon the systems (<15%) and not as a triggering factor for failure. Additionally, a number of suggestions regarding rock mass classification systems are given. Relatively, it is recommended rock cuttings to be classified according to their failure hazard taking into account both their condition and the influence of triggering factors upon stability. Moreover, each type of failure should be examined independently, as each one of them is governed by specific instability factors. Finally, some recommendations concerning amalgamation of factors, the possible ways that water may trigger a failure and the quantification of the most common triggering factors for failure (earthquake and precipitation) are provided.
Keywords: Rock mass rating (RMR); SMR; GSI; Rock mass classification systems; Rock slopes